1992
DOI: 10.1021/jo00031a008
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodifferentiating Z-E photoisomerization of cyclooctene sensitized by chiral polyalkyl benzenepolycarboxylates

Abstract: Highly efficient and unique enantiodifferentiating Z-E photoisomerization of cyclooctene (1) was achieved through singlet photosensitization with chiral polyalkyl benzenepolycarboxylates. Conversion dependence of optical yields and an attempted kinetic resolution of racemic (E)-isomer IE unequivocally showed that the enantiodifferentiating step is not the initial quenching of chiral sensitizer with enantiomeric IE but the rotational relaxation of planar 1Z to twisted singlet cyclooctene (1p) within the singlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 0 publications
3
71
0
1
Order By: Relevance
“…It has been demonstrated that this sensitized photoisomerization proceeds through a singlet exciplex 1 [Sens*•••1Z] [17] and that the enantiodifferentiation occurs upon rotational relaxation around the double bond of 1Z within the exciplex intermediate [8]. Thus, the relaxation process should be responsible for the temperature-switching behavior.…”
Section: Temperature Switchingmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that this sensitized photoisomerization proceeds through a singlet exciplex 1 [Sens*•••1Z] [17] and that the enantiodifferentiation occurs upon rotational relaxation around the double bond of 1Z within the exciplex intermediate [8]. Thus, the relaxation process should be responsible for the temperature-switching behavior.…”
Section: Temperature Switchingmentioning
confidence: 99%
“…Equation 1 indicates that the logarithm of k S /k R is proportional to reciprocal temperature, and that the activation parameters (∆∆H ‡ S-R and ∆∆S ‡ S-R ) can be calculated from the slope and intercept of the ln(k S /k R )-versus-1/T plot. Hence, the enantiodifferentiating photoisomerization of 1Z sensitized by a variety of chiral sensitizers was performed at several temperatures to give 1E in varying ee's, and the ln(k S /k R ) value was plotted against the reciprocal temperature to give an excellent straight line for each sensitizer [6][7][8][9]. Typical absolute ∆∆H ‡ S-R and T∆∆S ‡ S-R values obtained for non-ortho sensitizers are <0.1 and <0.2 kcal•mol -1 , respectively, while those for ortho sensitizers are as high as 0.5-1.1 and 0.5-3.5 kcal•mol -1 , respectively.…”
Section: Temperature Switchingmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4-Bis((À)-menthoxymethyl)benzene (2) 6 was prepared in 72% yield by the etheration of 1,4-bis(chloromethyl)benzene with (À)-menthol. The [4 + 2] cycloaddition of 2 with tetrafluorobenzyne according to a known procedure 5b,5c gave a 1 to 1 mixture of diastereomers, (R,R)-1 and (S,S)-1.…”
Section: B-2imentioning
confidence: 99%